Assessing Curriculum Design and Approaches for the Educational Studies Degree Path - Lynn, Payton (My University, 2024)
This paper presents a comprehensive proposal aimed at revising Kansas State University’s Educational Studies program in order to create a dynamic, interdisciplinary course of study for a diverse range of student interests and career aspirations. Drawing on insights from current students, peer institutions, and professional guidance, this proposal outlines the development of specialized pathways to provide a structured series of courses that allow students to align their studies with their individual career goals. The proposal prioritizes integrating additional minors and certificates to supplement students’ learning through interdisciplinary courses of study. Leveraging the research results, this proposal aims to help students feel academically and professionally prepared for their career in education.